Underwater and maritime archaeology in Latin America and the Caribbean - Leshikar-Denton, Margaret E. (One world archaeology ;, 2008)
Case studies written primarily by Latin American and Caribbean archaeologists demonstrate exciting and cutting edge research, conservation, site preservation, and interpretation of underwater and maritime archaeology in the region.